VALUASI EKONOMI SUMBERDAYA ALAM PANTAI SIDEM - Abdul Muqsith (Samakia : Jurnal Ilmu Perikanan, 2015)
This study was conducted in the coastal region Sidem Tulungagung in February 2015. The purpose of the research is to analyze the economic value of natural resources Sidem coast. This study used a survey method. Data collected by observation and interview respondents to identify and characterize patterns of resource use and to know the value of a measured resource of people's willingness to pay or accept a change of environment. Analysts data using economic valuation techniques to calculate the total economic value (Total Economic Value / TEV) of the fishery resources of coastal waters. The results of the analysis of the total economic value of natural resources is Sidem Beach Rp. 99,803,263,236. The economic contribution comes from fishing to reach 64.6 billion, or 64.7%. This arrest was made up of some fishing gear which nets titil, Fishing, Incamida (mesh bag), Beach seine and catching lobster. Followed from the tourism sector reached 19 billion (19%), and subsequently from the coconut tree reaching 14 billion (14.19%).